2010
DOI: 10.1111/j.1600-079x.2010.00788.x
|View full text |Cite
|
Sign up to set email alerts
|

Lowering intercellular melatonin levels by transgenic analysis of indoleamine 2,3-dioxygenase from rice in tomato plants

Abstract: Melatonin exists in numerous living organisms including vertebrates, insects, fungi, bacteria, and plants. Extensive studies have been conducted on the physiological roles of melatonin in various plant species. In plants, melatonin seems to act in antioxidant protection, as a growth promoter, and in photoperiodism. However, the mechanisms by which melatonin carries out these roles remain unclear. We manipulated the endogenous melatonin content in tomato plants by modifying the metabolic enzyme indoleamine 2,3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 51 publications
4
77
0
Order By: Relevance
“…Additionally, an effect of MEL on leaf and branching structures has been reported in both rice and tomato 103,104 . A general increase in total biomass due to MEL treatment has been reported, though this may just be a side effect of an increased production of roots, shoots or leaves 91,93,105 .…”
Section: Melatonin and Shoot Organogensismentioning
confidence: 97%
“…Additionally, an effect of MEL on leaf and branching structures has been reported in both rice and tomato 103,104 . A general increase in total biomass due to MEL treatment has been reported, though this may just be a side effect of an increased production of roots, shoots or leaves 91,93,105 .…”
Section: Melatonin and Shoot Organogensismentioning
confidence: 97%
“…Genetic manipulation of 2,3-dioxygenase revealed a new insight into the role of melatonin in plant development (Okazaki et al 2010). When the gene of 2,3-oxyganase isolated from rice was overexpressed in tomato, the melatonin level decreased, showing reduced numbers of lateral leaflets.…”
Section: Shoot Developmentmentioning
confidence: 99%
“…Numerous studies have shown that melatonin is widely involved in regulating both the biotic and abiotic stress tolerance, biological rhythms, plant growth and development (seed germination, root architecture, shoot development, plant flowering, fruit ripening, and yield; Kang et al, 2010; Okazaki et al, 2010; Wang et al, 2012; Byeon et al, 2013, 2014b; Yin et al, 2013; Zhang et al, 2013, 2014; Zhao et al, 2013; Byeon and Back, 2014a; Shi and Chan, 2014; Weeda et al, 2014; Shi et al, 2015a,b,c,d,e, 2016). …”
Section: Introductionmentioning
confidence: 99%